Forage seed market analysis in Vietnam - Bravo, Aura; Huyen, Le Thi Thanh; Dao Thu, Hang Thi; Pazos, Mateo; Triana, Natalia; Philp, Joshua; Atieno, Mary; Burkart, Stefan (2024)
The rapid expansion of animal-protein markets in Asia, coupled with the socioeconomic importance of livestock for communities in northern Vietnam, has further driven national and provincial governments to prioritize development policies aimed at modernizing and transforming the livestock sector (Dung et al., 2020; Decision No. 1520/QD-TTg issued on October 6, 2020 by the Prime Minister; Pham et al., 2020; Hansen, 2018). Consequently, technology-driven solutions and innovations aimed at improving the diets and nutrition of cattle, buffalo, and pigs have become essential to enabling the transition toward sustainable and inclusive livestock systems. The SAPLING initiative (Sustainable Animal Productivity for Livelihoods, Nutrition, and Gender Inclusion) under the CGIAR Initiative in Vietnam (2022 and 2024), aimed improve the value chains of pigs and cattle in the Northwest Highlands (NWH) region. To address the challenges of low productivity, the initiative targeted farmers by providing training on technical innovations in breeding, feed and forage management, and animal health. The Feed and Forages (F&F) component focused at transforming livestock feeding and nutrition practices to overcome challenges such as feed shortages during winter and dry seasons, the low nutritional quality of livestock feed (often reliant on native pastures and crop residues), and the lack of knowledge and skills in forage management and feed technologies (Hammond et al., 2021; Tran et al., 2023).